Do Subnational Governments Fund Organizations in Neoliberal Times? The Role of Critical Events in Provincial Funding of Women's Organizations. (November 2017) - Kay, Emma; Ramos, Howard
Countries around the world have adopted neoliberal or austerity policies. Among states that fund organizations, this may have a detrimental effect on civil society. Looking at the Canadian context, this article examines whether subnational governments, provinces, step in during times of national budget cuts and changing political environments to fund organizations. We do this by analyzing the effect of critical events, regime changes, and the founding of key organizations on state funding in the province of Nova Scotia between 1960 and 2014. We do this to examine how the interaction of national and subnational political context shapes subnational funding of organizations. We find that critical events appear to be linked to increases in provincial funding, however, do not appear to be linked to cuts in funding. Regime changes and founding of key organizations have less clear-cut relationships with provincial funding.